Impact of COVID-19 Pandemic on Redang and Perhentian Island Communities Behavioral Strategy - MOHAMAD, Zaleha; NASIR, Aslina; RASHID, Noorhaslinda Kulub Abd; BACHOK, Zainudin (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023DO - 10.14505/jemt.v14.3(67).10, 2023)
Pandemic COVID-19 did not only affect the tourism activities and income of islands in Negeri Terengganu but their behaviours after pandemic also changed especially B40 communities in Redang and Perhentian Islands.This study is to determine the impact of COVID-19 pandemic shock on Redang and Perhentian Island communities’ behavioral strategy. The regression analysis was performed into 4 models. Model 1i and 1ii were conducted to determine the impact of COVID-19 pandemic shock on communities’ behavioral strategy in Redang and Perhentian Island, respectively. Meanwhile, model 2i and 2ii were to determine the impact of pandemic shock’s components on communities’ behavioral strategy. The findings showed that 25.2% and 39.3% behavioral strategy are explained by pandemic shock in Redang and Perhentian Island, respectively. Besides, 34.3% and 47.8% of behavioral strategy respondents in Redang and Perhentian Island are explained by economy shock, health shock, politic shock and risk management, respectively. Furthermore, the economic shock is dominant factor affecting the behavioural strategy among respondents in Redang Island to overcome problem regarding expenditure and spiritual practice, followed by risk management and health shock. Whereas economic shock is also dominant factor affecting the behavioural strategy among respondents in Perhentian Island, followed by health shock, risk management and environmental shock.